Teenagers knowledge about teenage pregnancy prevention - Lima, Antonny; Pessoa, Beatriz Reis; da Silva, Bruna Costa; Facundo, Maria Lua Matos; Rodrigues, Railda Lima; da Silva, Maria Beatriz Pereira; Arraes, Andressa Silva (Disciplinarum Scientia | Saúde, 2024)
The present study aimed to assess teenagers’ knowledge about teenage pregnancy prevention. Since pregnancy during this period becomes a condition that increases the prevalence of maternal, fetal, and neonatal complications, as well as exacerbating existing socioeconomic problems. Therefore, nurses, through the School Health Program, should develop actions that promote prevention, autonomy, and self-care, encouraging adolescents to act in the name of their health and well-being, and in guaranteeing their rights. This is a descriptive study with a quantitative approach, involving students aged 15 to 17 from a public school in the city of São Luís Gonzaga do Maranhão, totaling 20 teenagers. Data were collected through the application of a questionnaire with 19 closed questions on the study topic to the students, which were then analyzed and organized into Excel 2016 spreadsheets using the statistical frequency calculation method and presented in tables and graphs. The results highlight that 70% of the participants are female; 25% reported being sexually active, and 85% demonstrated knowledge of contraceptive methods, with condoms being the most mentioned. It is concluded that the implications of this research may contribute to the reconsideration of many actions within the municipality, encouraging nurses to provide assistance beyond Basic Health Units, as well as to analyze more effectively the pregnancy rates and the attitudes being taken to address this problem.